PENGARUH LINGKUNGAN KERJA, ETOS KERJA DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA DINAS BINA MARGA PROPINSI SULAWESI TENGAH - Saleha, Saleha (Katalogis, 2016)
This research intends to explore and analyze simultaneous and partial impacts workenvironment, work ethics, and work culture on employee performance in Bina Marga Agency of Central Sulawesi. It Involves 116 employees as respondentsand applies multiple linear regressions analysis with descriptive approach. The results show that work environment, work ethics, and work culture simultaneously and partially have significant influence on employees’performance in Bina Marga Agency of Centra Sulawesi